Analysis of the Influence of Corporate Social Responsibility and Corporate Governance on Financial Performance in Mining Companies Mediated by Green Innovation - Marheni, Dewi Khornida; Cheristina, Cheristina; Candy, Candy (Almana : Jurnal Manajemen dan Bisnis, 2024)
Financial performance is influenced by several factors, namely corporate social responsibility and corporate governance, which are mediated by green innovation. This study uses a quantitative method. The data collection type for this research is secondary data. The sample used in the research consists of mining companies. The analysis method used in this study is Panel Regression. The purpose of this research is to analyze the effect of corporate social responsibility and corporate governance on financial performance mediated by green innovation. Financial performance is the dependent variable, corporate social responsibility and corporate governance are the independent variables, and green innovation is the mediating variable. The results of this study show that corporate social responsibility has a significant positive effect on financial performance. Corporate governance does not have a significant effect on financial performance. Green innovation did not successfully mediate the relationship between corporate social responsibility and corporate governance on financial performance.